2018
DOI: 10.1021/acscatal.7b04209
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of B(C6F5)3-Catalyzed Selective Deoxygenation of 1,2-Diols: Cyclic and Noncyclic Pathways

Abstract: The selective deoxygenation of polyols has emerged as an attractive approach to transform biomass-derived polyols into valuable building blocks. Herein, we present a theoretical study on the boron-catalyzed selective deoxygenation of terminal 1,2-diols. The computational results explain the different product distributions obtained with different silanes and unveil the critical role of the cyclic siloxane intermediate. Compared to noncyclic pathways, the cyclic pathway facilitates the initial deoxygenation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…[46] The Piers-Rubinsztajn reaction also proceeds via asimilar S N 2-Si transition statet of orm ad isilyl oxonium ion intermediate (Scheme 14). [47] The S N 2S im echanism explains well that the undesired Piers-Rubinsztajn reactions with monohydrosilanes are kinetically unfavorable, on account of steric hindrance of the isopropoxysilanes. Although cleavage of the CÀ Ob ond in the disilyl oxonium ion through nucleophilic attack of the borohydrideH ÀB(C 6 F 5 ) 3 À affords the desired siloxane (Scheme 14, path A), cleavageo ft he SiÀOb ond leads to the reverser eaction or alkoxysilane/hydrosilane metathesis, which eventually resultsi nu ndesired side reactions (path B).…”
Section: One-pot Iterative Synthesis Of Sequence-specific Oligosiloxanesmentioning
confidence: 98%
See 1 more Smart Citation
“…[46] The Piers-Rubinsztajn reaction also proceeds via asimilar S N 2-Si transition statet of orm ad isilyl oxonium ion intermediate (Scheme 14). [47] The S N 2S im echanism explains well that the undesired Piers-Rubinsztajn reactions with monohydrosilanes are kinetically unfavorable, on account of steric hindrance of the isopropoxysilanes. Although cleavage of the CÀ Ob ond in the disilyl oxonium ion through nucleophilic attack of the borohydrideH ÀB(C 6 F 5 ) 3 À affords the desired siloxane (Scheme 14, path A), cleavageo ft he SiÀOb ond leads to the reverser eaction or alkoxysilane/hydrosilane metathesis, which eventually resultsi nu ndesired side reactions (path B).…”
Section: One-pot Iterative Synthesis Of Sequence-specific Oligosiloxanesmentioning
confidence: 98%
“…Oestreich and Rendler experimentally demonstrated that the B(C 6 F 5 ) 3 ‐catalyzed hydrosilylation of ketones proceeded via an S N 2 Si transition state triggered by Si−H bond activation by B(C 6 F 5 ) 3 ; a mechanism that is supported by DFT calculations . The Piers–Rubinsztajn reaction also proceeds via a similar S N 2‐Si transition state to form a disilyl oxonium ion intermediate (Scheme ) . The S N 2 Si mechanism explains well that the undesired Piers–Rubinsztajn reactions with monohydrosilanes are kinetically unfavorable, on account of steric hindrance of the isopropoxysilanes.…”
Section: One‐pot Iterative Synthesis Of Sequence‐ Specific Oligosiloxmentioning
confidence: 99%
“…Communications bond reduction (see the Supporting Information) and lower than that of similarly calculated C À O bond reductions involving BCF/HSiR 3 . [33] The data suggest that a chair flip to the 1 C 4 conformer is required to minimize steric clashes between neighboring -OSi groups ( Figure S2). An analysis of the coupling constants ( 3 J HH ) showed that Et 3 Si-1-deoxyglucose and A adopt the 4 C 1 and 1 C 4 conformers, respectively ( Figures S3 and S4), consistent with the computed conformer stabilities.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…Zuschriften bond reduction (see the Supporting Information) and lower than that of similarly calculated C À O bond reductions involving BCF/HSiR 3 . [33] The data suggest that a chair flip to the 1 C 4 conformer is required to minimize steric clashes between neighboring -OSi groups ( Figure S2). An analysis of the coupling constants ( 3 J HH ) showed that Et 3 Si-1-deoxyglucose and A adopt the 4 C 1 and 1 C 4 conformers, respectively ( Figures S3 and S4), consistent with the computed conformer stabilities.…”
Section: Angewandte Chemiementioning
confidence: 98%